GAYA KEPEMIMPINAN WIRAUSAHA DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UKM MELALUI MEDIASI KEUNGGULAN BERSAING - Maulana, Uray Andrey Indra; Hendharsa, Angga; Rawa, Ricola Dewi; Arweni, Arweni; Kariza, Cesy Iola (Jurnal Manajemen dan Kewirausahaan, 2024)
This study aims to determine the effect of entrepreneurial leadership, orientation, and competitive advantage on SME’s performance. The population in this study were SMEs in Pontianak City, totaling 1,894 SMEs. The sampling technique used a simple random sampling method using the calculation of Isaac and Michael obtained a sample size of 380 respondents. The quantitative research method uses PLS-SEM data analysis techniques and analysis tools using WarpPls 8.0. The results of the study state that entrepreneurial leadership, entrepreneurial orientation, and competitive advantage significantly affect the performance of SMEs. This study found that the competitive advantage variable is a partial mediating variable.